Analisis Pengaruh Likuiditas, Solvabilitas dan Profitabilitas Terhadap Price Earning Ratio pada Perusahaan Food and Beverage yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2016-2020 - Magrita Krisantini Werang; Gendro Wiyono; Pristin Prima Sari (J-MAS (Jurnal Manajemen dan Sains), 2023)
The purpose of this study was to determine the Effect Analysis of Liquidity, Solvency and Profitability on Price Earning Ratio in Food and Beverage Companies listed on the Indonesia Stock Exchange (IDX) from 2016 to 2020. The population used in this study were Food and Beverage Companies listed on the Stock Exchange. Indonesian Securities (IDX) 2016-2020. This study uses purposive sampling technique. The number of samples in this study amounted to 14 samples, which were obtained from secondary data using the documentation method. The data analysis technique used in this study was multiple linear regression and hypothesis testing (F test and t test) with an alpha significance level of 5%. The results of this study indicate that the variable liquidity (Current Ratio) and profitability (Return On Equity) have a positive and significant effect on the price earning ratio. While the solvency variable (Debt to Equity Ratio) has no significant effect on the price earning ratio and simultaneously shows that there is an influence between liquidity, solvency and profitability on the price earning ratio. This research is limited to food and beverage companies listed on the IDX. So for future researchers it is suggested to extend the research and expand the number of research populations. As well as considering other variables that might affect the Price Earning Ratio.